Mechanisms of irreversible decoherence in solids - Domínguez, Federico Daniel; Zamar, Ricardo César; Segnorile, Héctor Hugo; González, Cecilia Elida (2024)
Artículo finalmente publicado en: Domínguez, F. D., Zamar, R. C., Segnorile, H. H. y González, C. E. (2017). Mechanisms of irreversible decoherence in solids. Physical Review B, 95 (22), 224423. https://doi.org/10.1103/PhysRevB.95.224423